Pemaknaan Bumi Berbicara Menurut Mufasir Klasik dan Modern - Rizqiya Irfana; Abdul Malik Ghazali; Yusuf Baihaqi (Refleksi, 2022)
In the development of Quran interpretation, the approach of science has been used, which is considered the most contemporary approach to understanding verses related to the universe. Among the paradigm shifts in the interpretation of the Quran caused by the use of a scientific approach, is the emergence of an understanding of verses that were originally associated with a certain time, such as the impending apocalypse, then changed that in fact the verse is not an explanation of the events of the doomsday, such as the change in understanding of verse 4 in sura al-Zalzalah which states that at the time of the earthquake, the earth speaks to man. This article is a results of the research on the tafsir al-Jāmi’ li Ahkām al-Qur’ān by imam al-Qurṭubī and Kitab Al-Qur’an dan Tafsirnya (Edisi yang Disempurnakan) compiled by the Ministry of Religion of the Republic of Indonesia by qualitative methods. This article concludes that classical and modern exegetes have similarities in interpreting the earth speak. The equation is that when the earth is shaken it releases its burden in the form of rocks and other objects. After examining these objects, they can provide information about human actions that have occurred at certain times. The Geologists can also get information about when the earthquake occurred at a certain time from the records found on rocks and coral reefs.